2002
DOI: 10.1038/sj.cdd.4401055
|View full text |Cite
|
Sign up to set email alerts
|

Key role of mitochondria in cerulenin-mediated apoptosis

Abstract: Cerulenin, a fungal metabolite, is known to be a specific inhibitor of fatty acid synthase. Here we report that cerulenin is an effective inducer of apoptosis in different wild-type p53 and mutant p53 tumor cell lines, whereas normal human keratinocytes and fibroblasts are resistant to the apoptotic effect. To get more insight into the mechanisms of how cerulenin induces apoptosis we investigated several signal transduction molecules, including p53, p73, p21/WAF1, Bax, cytochrome c, and caspases 3 and 9. Our d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
0
12

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 28 publications
5
42
0
12
Order By: Relevance
“…To investigate further the apoptotic response, the role of the death receptor pathway in cerulenin-mediated apoptosis was evaluated by infecting glioma cells with a FADD-DN adenovirus. In agreement with the previously suggested mechanism involving cytochrome c release (Heiligtag et al, 2002) FADD-DN, which inhibits all the known death receptor pathways, had no effect on cerulenin-induced glioma cell death.…”
Section: Hindiii (557)supporting
confidence: 91%
See 1 more Smart Citation
“…To investigate further the apoptotic response, the role of the death receptor pathway in cerulenin-mediated apoptosis was evaluated by infecting glioma cells with a FADD-DN adenovirus. In agreement with the previously suggested mechanism involving cytochrome c release (Heiligtag et al, 2002) FADD-DN, which inhibits all the known death receptor pathways, had no effect on cerulenin-induced glioma cell death.…”
Section: Hindiii (557)supporting
confidence: 91%
“…In our experiments, we demonstrated clearly that PARP cleavage, an apoptotic marker, was induced in cerulenin-treated U251 and SNB-19 cells; this was associated with significant cytotoxicity. Heiligtag et al (2002) reported that cerulenin is an effective inducer of apoptosis in WT or mutant p53 neuroblastoma, melanoma, and colon carcinoma cell lines; normal human cells were resistant to cerulenin-induced apoptosis. Further, apoptosis was mediated both by overexpression of proapoptotic Bax, in a p53-independent manner, and by a rapid release of mitochondrial cytochrome c, leading to activation of caspase 3 and 9.…”
Section: Hindiii (557)mentioning
confidence: 99%
“…As p53 activation has been associated with the FASN inhibition-induced apoptosis in colon carcinoma, neuroblastoma, and breast cancer cell lines, 22,27 we sought to verify the effect of pifithrin-alpha, an inhibitor of p53 activation, on the apoptotic rates of B16-F10 cells. In the studied conditions, apoptosis was not prevented by p53 inhibition (Figure 5b), indicating that this tumor suppressor protein is not involved in the apoptosis triggered by the lack of an efficient endogenous fatty acid synthesis.…”
Section: B16-f10 Cells By Elisamentioning
confidence: 99%
“…26 Mitochondrial involvement, evidenced by increased levels of the pro-apoptotic protein Bax and cytochrome c release, was shown in tumor cell lines following pharmacological FASN inhibition. 27,28 Despite the fact that the expression of a dominant-negative mutant p53 increases sensitivity of colon carcinoma cells to FASN inhibitors, 22 FASN inhibition-induced apoptosis was described as p53 independent. 27 Malignant melanoma is a chemotherapy-resistant aggressive tumor derived from melanocytes of the skin and, less frequently, oral mucosal membranes.…”
mentioning
confidence: 99%
See 1 more Smart Citation